The Response of the Gut Microbiota to Dietary Changes in the First Two Years of Life - Li, Yichen; Faden, Howard S.; Zhu, Lixin (Frontiers in Pharmacology, 2020)
The infant gut microbiota undergoes significant changes in the first two years of life in response to changes in the diet. The discontinuation of the milk-based diet of the first year and the introduction of solid foods in the second year of life results in a decline in bifidobacterium, a shift from infant strains of bifidobacterium to adult strains which preferentially metabolize oligosaccharides derived from plants rather than from milk, a surge in short chain fatty acids such as acetic, propionic and butyric acid from newly acquired commensal clostridium, and the transformation of primary bile acids into secondary bile acids by a limited number of newly acquired and highly specialized Clostridium spp. By three years of age, diet and gut microbiota closely resemble those of adults. Gut bacteria required for the production of SCFAs and secondary BAs are potential targets for the intervention of microbiome-related diseases.